GAMIFICATION IN EDUCATION: CHANGING THE ATTITUDE OF MEDICAL STUDENTS TOWARDS DEMENTIA BY USING VIRTUAL REALITY (PILOT STUDY) - Kollar, Janos (PUPIL: International Journal of Teaching, Education and Learning, 2020)
The aim of the study was to change the attitudes of medical students towards elderly people with dementia in a positive way and to raise awareness of the importance of studying dementia in the elderly by using virtual reality tools. Hungarian (n = 20) and foreign (n = 20) medical students could experience what it would be like to be an elderly, demented person for 5 minutes by using a virtual reality application. Before and after the experiment, they completed a questionnaire and expressed their opinion on a Likert scale (0-6 points). The evaluation was made by using the Wilcoxon signed-rank test. The attitude of foreign and Hungarian medical students changed significantly in a positive way regarding the importance of studying dementia in the elderly (Z = 18, p < 0.078 and Z = 7.5, p < 0.187 respectively), judging the difficulty of lives of elderly people with dementia (Z = 20, p < 0.0078 and Z = 27.5, p < 0.002 respectively), judging their empathy for elderly people with dementia (Z = 32, p < 0.00112 and Z = 55.5, p < 0.0005 respectively), understanding thinking of elderly people with dementia (Z = 79 p < 0.0001 and Z = 59, p < 0.026 respectively), regarding the likelihood of taking steps to prevent their own dementia (Z = 27.5 p < 0.002 and Z = 27.5, p < 0.002 respectively). The study demonstrated the importance and the effectiveness of applying virtual reality tools in educating medical students.